Memory, slavery, and plantation museums: the River Road Project. Issue 3 (2nd July 2016) - Alderman, Derek H.; Butler, David L.; Hanna, Stephen P.
ABSTRACT: Heritage tourism plays an increasingly important yet controversial role in interpreting the emotionally and politically charged memories and legacies of African enslavement. Antebellum plantation museums in the southeastern USA remain relatively underanalyzed by researchers, despite their tradition of ignoring and minimizing the contributions and struggles of the slave community. Yet, this neglect is being challenged somewhat by a growing number of plantations and counter-narrative sites that incorporate slavery into docent-led tours, promotional materials, exhibits, and preserved structures. Responding to a need for scholarship that can ferret out the nuances, complexities, and conflicts of producing and consuming heritage at these tourist sites, this special issue presents the results of a study of four plantations (Laura, Oak Alley, Houmas House, San Francisco) along Louisiana's River Road. The issue's editors and contributing authors address a central question: what factors, social actors, and interactions (social and spatial in nature) shape, facilitate, or even constrain the remembering of slavery at southern plantation museums, including those sites making seemingly significant progress in recovering the enslaved? River Road is a microcosm of the larger politics of reshaping southern and American heritage tourism and demonstrates the value of industry-engaged, multi-method examinations of different plantation landscapes within the same region.